DEVELOPMENT OF LAND CONSOLIDATION MODELS FOR AGRICULTURAL IN DEALING WITH INDUSTRIAL WASTE DISEASES (CASE STUDY: RANCAEKEK DISTRICT) - Ihsan, Muhammad (Universitas Pendidikan Indonesia, 2017)
The agricultural areas in Rancaekek sub-district are exposed to industrial liquid waste so that soil and water quality decreases. One solution in tackling industrial waste is phytoremediation. The area required for phytoremediation development using Reed method is 2,426.14 hectares. Land preparation for phytoremediation development can be done through land consolidation. In this research, there are three consolidation models. Models 1 and 2 produce models with the same land donation, i.e. 7% of the total area. In model 3 the land donation ranges between 6-8% of the initial plot area. The closer to the remediation center, the greater the land donation will be. To get maximum benefit, phytoremediation development can be built to cover the whole agricultural area.